Full-length and N-terminally truncated recombinant interleukin-38 variants are similarly inefficient in antagonizing interleukin-36 and interleukin-1 receptors - Alejandro Diaz-Barreiro; Dominique Talabot-Ayer; Arnaud Huard; Gea Cereghetti; Jenna Tonacini; Mike Maillasson; Antonio Francés-Monerris; Erwan Mortier; Gaby Palmer (Cell Communication and Signaling)
Abstract Background Interleukin (IL)-38 is an IL-1 family cytokine that was proposed to exert anti-inflammatory effects. However, its mechanisms of action are not well understood and the identity of the IL-38 receptor(s) remains debated. Proposed candidates include the IL-1 receptor (IL-1R1), the IL-36 receptor (IL-36R) and the orphan receptor IL-1RAPL1. Yet, in literature, IL-38 is often presented as an IL-36R antagonist. Methods The N-terminus of the IL-38 protein produced in a human keratinocyte cell line and of endogenous epidermal IL-38 isolated from healthy human skin was characterized by mass spectrometry. The effects of various recombinant forms of IL-38 on IL-36R- and IL-1R1-mediated responses were assessed in IL-36R HEK Blue reporter cells and in a normal human keratinocyte cell line. IL-8 and IL-6 production was quantified by ELISA. Binding of recombinant IL-38 proteins to the IL-36R was assessed by surface plasmon resonance. Results Analysis of its native N-terminus revealed that the IL-38 protein produced by human keratinocytes starts at cysteine 2. In cell-based assays, neither full-length amino acid 2-152 IL-38 nor two N-terminally truncated forms of the protein showed efficient antagonist activity on IL-36R- and IL-1R1-mediated responses. The recombinant IL-38 proteins bound to the IL-36R with only moderate affinity, which may provide a mechanistic explanation for inefficient IL-36R antagonism. Conclusions Our results argue against meaningful inhibitory effects of any of the recombinant IL-38 variants tested on IL-36R or IL-1R1-mediated responses. The mechanisms underlying reported anti-inflammatory effects of IL-38 are thus still unclear, but seem unlikely to be mediated by classical IL-36R or IL-1R1 antagonism.